2021
DOI: 10.3390/ma14092305
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Monomer, Crosslinking Agent, and Filler Concentrations on the Viscoelastic and Swelling Properties of Poly(methacrylic acid) Hydrogels: A Comparison

Abstract: The present work aims at comparatively studying the effects of the concentrations of a monomer (10–30 wt% based on the whole hydrogel composition), crosslinking agent (1–3 mol% based on the monomer), and reinforcing agent (montmorillonite–MMT, 1–3 wt.% based on the whole hydrogel composition) on the swelling and viscoelastic properties of the crosslinked hydrogels prepared from methacrylic acid (MAA) and N,N′-methylenebisacrylamide (BIS) in the presence of K2S2O8 in aqueous solution. The viscoelastic measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…In a strong acidic environment (pH 1.2), the reinforced hydrogels swelled less than H, most likely because of the slight crosslinking effect of the fillers [ 44 ]. The additional crosslinking effect induced by the filler could be best identified at this pH because no COO − groups formed due to the basicity of the medium or the reinforcing agent being present ( Figure 1 ) [ 43 , 45 , 58 ]. An estimation of the structural parameters of the hydrogels at this pH (Equations (2)–(5)) showed an increase in the crosslinking density ( ) as a function of the filler (H < HMt < HXLG ≈ HXLS < HHDK ≈ HFS, Table 3 ), probably determined by the number of additional PMAA network-reinforcing agent interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a strong acidic environment (pH 1.2), the reinforced hydrogels swelled less than H, most likely because of the slight crosslinking effect of the fillers [ 44 ]. The additional crosslinking effect induced by the filler could be best identified at this pH because no COO − groups formed due to the basicity of the medium or the reinforcing agent being present ( Figure 1 ) [ 43 , 45 , 58 ]. An estimation of the structural parameters of the hydrogels at this pH (Equations (2)–(5)) showed an increase in the crosslinking density ( ) as a function of the filler (H < HMt < HXLG ≈ HXLS < HHDK ≈ HFS, Table 3 ), probably determined by the number of additional PMAA network-reinforcing agent interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Laponite XLG and Laponite XLS (BYK Additives & Instruments, kindly donated by Cosichem & Analytical, Romania), the two commercial brands of hydrophilic pyrogenic silica (fumed silica, FS, Sigma and HDK N20 pyrogenic silica, HDK, Wacker Silicones), methacrylic acid (MAA, Jansen Chemistry, 99%), N,N’-methylenebisacrylamide (BIS, 99%, Sigma Aldrich), ammonium persulfate (APS, Sigma Aldrich, 98%), methylene blue (MB, Loba Chemie, 95%), and crystal violet (CV, Loba Chemie, 96%) were used as received. Unmodified montmorillonite (Mt, Cloisite Na, a gift from Southern Clay Products Inc. Gonzales, TX, USA) was purified by the method previously described [ 43 ]. The characteristics of both reinforcing agents in water and their aqueous dispersions, determined by us, are displayed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, results depict that, with the increase in crosslinker concentration, the swelling index of the hydrogel ultimately decreased. However, Ninciuleanu et al reported that with the increase in MBA concentration (crosslinker), the swelling degree of the hydrogel increased due to the higher crosslinking density [26]. The water absorption capacity of the hydrogel was lower as a result of more crosslinking agent.…”
Section: Effect Of Crosslinker (Mba) On Hydrogel Swellingmentioning
confidence: 99%
“…Hence, such a process can affect cell spreading, migration, proliferation, and differentiation, thus impacting tissue regeneration. The rate of degradation can be tuned by altering the ratio of crosslinker to monomer during synthesis [ 61 ]. In PNIPAm-based copolymeric scaffold synthesis, degradation time can be regulated by tuning the ratio of PNIPAm polymer to another polymer [ 62 ].…”
Section: Scaffolds For Cartilage Regenerationmentioning
confidence: 99%